1999
DOI: 10.1152/ajpendo.1999.277.6.e1032
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin inhibits androgen response to chorionic gonadotropin in humans

Abstract: Eicosanoids play an important role in the regulation of the hypothalamic-pituitary axis; less clear is their role in testicular steroidogenesis. To evaluate the involvement of cyclooxygenase metabolites, such as prostaglandins, in the regulation of human testicular steroidogenesis, we examined the effects of a prostaglandin-blocker, aspirin, on plasma testosterone, pregnenolone, progesterone, 17OH-progesterone, androstenedione, dehydroepiandrosterone, and 17beta-estradiol response to human chorionic gonadotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…This is in contrast to the human data, where ibuprofen, as the most potent PG synthesis inhibitor, was associated with the highest risk of congenital cryptorchidism. Acetylsalicylic acid has previously been shown to partially block the increase in testosterone production after hCG stimulation of adult men (Conte et al, 1999). A similar scenario is plausible during fetal development, which could account for the anti-androgenic effect.…”
Section: Discussionmentioning
confidence: 84%
“…This is in contrast to the human data, where ibuprofen, as the most potent PG synthesis inhibitor, was associated with the highest risk of congenital cryptorchidism. Acetylsalicylic acid has previously been shown to partially block the increase in testosterone production after hCG stimulation of adult men (Conte et al, 1999). A similar scenario is plausible during fetal development, which could account for the anti-androgenic effect.…”
Section: Discussionmentioning
confidence: 84%
“…Whereas few data are available on the possible effects of therapeutic doses of inhibitors of prostaglandins synthesis (such as for example the non-steroidal anti-inflammatory drugs) on the endocrine systems [7][8][9]. Recent studies have shown that some NSAIDs, such as for example the aspirin, influence the steroids secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that some NSAIDs, such as for example the aspirin, influence the steroids secretion. In particular they have observed that the acetylsalicylic acid is able to inhibit both stimulated testosterone and other androgens secretion after human chorionic gonadotropin administration in healthy sedentary males and stress-related adenoorticotropin hormone and cortisol in healthy male athletes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…But these studies involved use of APAP use over an extensive period of time; so more relevant studies should be conducted to explore whether the shorter dose also has the similar effects. Since studies conducted on this are animal studies, more studies are needed to find out how usefully this information can be transferred to human studies [44,45].…”
Section: Acetaminophen Exposure and Female Fertility Conclusionmentioning
confidence: 99%